PEMBELAJARAN IPS BERBASIS KOMUNITAS DAN KEARIFAN LOKAL - Rahma Awalia; Sirajuddin Saleh; Nurfadillah Sjarif; Widya Anugrah Rusdi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social Studies Education in Indonesia faces a crisis of meaning due to the dominance of rote learning and the lack of connection to students’ social realities. This study examines the concepts, implementation, challenges, and solutions of community-based learning and local wisdom approaches in Social Studies Education through a systematic literature review of journal articles, master’s theses, and Merdeka Curriculum policy documents. The findings reveal that this approach is grounded in critical pedagogy, social constructivism, and ethnopedagogy. Its implementation through field studies, service learning projects, and community-based problem solving has been shown to improve conceptual understanding, cultural identity, social empathy, and students’ learning motivation. The main challenges include curriculum density, limited teacher competence, lack of community support, financial constraints, and the decline of local wisdom. Proposed solutions include project-based learning integration, teacher training, collaboration with communities, optimization of school operational funds, and digital documentation of local culture to support national cultural preservation in the era of globalization.